Energetic and exergetic analysis of combined cycle power plant: Part-1 operation and performance - Almutairi, Abdulrahman S.; Pilidis, Pericles; Al-Mutawa, Nawaf (MDPI, 2015)
Energetic and exergetic analyses are conducted using operating data for Sabiya, a combined cycle power plant (CCPP) with an advanced triple pressure reheat heat recovery steam generator (HRSG). Furthermore, a sensitivity analysis is carried out on the HRSG using a recent approach to differentiate between the sources of irreversibility. The proposed system was modelled using the IPSEpro software and further validated by the manufacturer’s data. The performance of the Sabiya CCPP was examined for different climatic conditions, pressure ratios, pinch point temperatures, high-pressure steam, and condenser pressure values. The results confirmed that 60.9% of the total exergy destruction occurs in the combustion chamber, which constitutes the main source of irreversibilities within a system. The exergy destruction was significantly affected by both the pressure ratio and the high-pressure steam, where the relation between them was seen to be inversely proportional. The high-pressure stage contributes about 50% of the exergy destruction within the HRSG compared to other stages and the reheat system, due to the high temperature difference between the streams and the large number of components, which leads to high energy loss to the surroundings. Numerous possibilities for improving the CCPP’s performance are introduced, based on the obtained results.
Keywords: combined cycle; heat recovery steam generator (HRSG); reheat; exergy; destruction